Bimbingan Teknis Penyusunan Anggaran Operasional Koperasi Simpan Pinjam dan Koperasi Konsumen Bagi Pengurus Koperasi di Jawa Barat - Wahyuningsih, Endang (LPPM Universitas Koperasi Indonesia, 2024)
Professional business management includes, among other things, implementing management functions correctly and precisely. One of the fundamental management functions is preparing rational, detailed, and measurable planning. For this reason, all cooperative managers must be able to prepare plans, both work program plans and financial plans to implement the work program, which is often called the cooperative income and expense budget. This reason is one of the reasons for providing technical guidance carried out by the West Java Province Cooperative Education and Training Center with material including the preparation of the Cooperative Work Plan and Revenue and Expenditure Budget (RKAPBK). The work plan is prepared according to the type of cooperative activity, which in this case is consumer cooperatives and savings and loan cooperatives. If the cooperative has activities related to the financial services business, then all management, including the preparation of the RKAPBK, must be made separately. This is absolutely necessary because financial services businesses are financial sector businesses and trading businesses are real sector business activities. In the financial services business of savings and loan cooperatives, money is a product whose benefits are taken, which will generate income over time. Meanwhile, in the real business sector, the products being traded are goods and money is the means of payment. For this reason, in this technical guidance, the RKAPBK case for financial sector businesses in Savings and Loans Cooperatives and the RKAPK case for the real sector business of Consumer Cooperatives are discussed.